JP1 : Art International. - Paleis voor Schone Kunsten, Brussel (Brussel : Jeune Peinture Belge, 1975)
Anthoons, Willy ; Barbaix, René ; Bonnet, Anne ; Bertrand, Gaston ; Collignon, George ; Cox, Jan ; Delahaut, Jo ; Godderis, Jack ; Van Lint, Louis ; Lismonde, Jules ; Mahy, Emile ; Mendelson, Marc ; Milo, Jean ; Mortier, Antoine ; etc.
JP1, Art International / Internationale Kunst, Paleis voor Schone Kunsten, Brussel, 18.7 - 31.8.1975
boek